The clinical meaning of external cervical resorption in maxillary canine: transoperative dental trauma - Alberto Consolaro; Mauricio de Almeida Cardoso; Carolina Dornelas C. M. de Almeida; Ingrid Araújo Oliveira Souza; Leopoldino Capelloza Filho (Dental Press Editora, 2014)
External Cervical Resorption in maxillary canines with pulp vitality is frequently associated with dental trauma resulting from surgical procedures carried out to prepare the teeth for further orthodontic traction. Preparation procedures might surgically manipulate the cementoenamel junction or cause luxation of teeth due to applying excessive force or movement tests beyond the tolerance limits of periodontal ligament and cervical tissue structures. Dentin exposure at the cementoenamel junction triggers External Cervical Resorption as a result of inflammation followed by antigen recognition of dentin proteins. External Cervical Resorption is painless, does not induce pulpitis and develops slowly. The lesion is generally associated with and covered by gingival soft tissues which disguise normal clinical aspects, thereby leading to late diagnosis when the process is near pulp threshold. Endodontic treatment is recommended only if surgical procedures are rendered necessary in the pulp space; otherwise, External Cervical Resorption should be treated by conservative means: protecting the dental pulp and restoring function and esthetics of teeth whose pulp will remain in normal conditions. Unfortunately, there is a lack of well-grounded research evincing how often External Cervical Resorption associated with canines subjected to orthodontic traction occurs.